Bridging basic science and applied diagnostics: Comprehensive viral diagnostics enabled by graphene-based electronic biosensor technology advancements - Herdina, Anna Nele; Bozdogan, Anil; Aspermair, Patrik; Dostalek, Jakub; Klausberger, Miriam; Lingg, Nico; Cserjan-Puschmann, Monika; Aguilar, Patricia Pereira; Auer, Simone; Demirtas, Halil; Andersson, Jakob; Lötsch, Felix; et al. (Biosensors & bioelectronics, 2025)
This study presents a graphene field-effect transistor (gFET) biosensor with dual detection capabilities for SARS-CoV-2: one RNA detection assay to confirm viral positivity and the other for nucleocapsid (N-)protein detection as a proxy for infectiousness of the patient. This technology can be rapidly adapted to emerging infectious diseases, making an essential tool to contain future pandemics. To detect viral RNA, the highly conserved E-gene of the virus was targeted, allowing for the determination of SARS-CoV-2 presence or absence using nasopharyngeal swab samples. For N-protein detection, specific antibodies were used. Tested on 213 clinical nasopharyngeal samples, the gFET biosensor showed good correlation with RT-PCR cycle threshold values, proving its high sensitivity in detecting SARS-CoV-2 RNA. Specificity was confirmed using 21 pre-pandemic samples positive for other respiratory viruses. The gFET biosensor had a limit of detection (LOD) for N-protein of 0.9 pM, establishing a foundation for the development of a sensitive tool for monitoring active viral infection. Results of gFET based N-protein detection corresponded to the results of virus culture in all 16 available clinical samples and thus it also proved its capability to serve as a proxy for infectivity. Overall, these findings support the potential of the gFET biosensor as a point-of-care device for rapid diagnosis of SARS-CoV-2 infection and indirect assessment of infectiousness in patients, providing additional information for clinical and public health decision-making.
Keywords: grafit; Equipment Design; SARS-CoV-2; fosfoproteiny; nazofarynx; RNA, Viral; lidé; koronavirové nukleokapsidové proteiny; Graphite; Phosphoproteins; Coronavirus Nucleocapsid Proteins; COVID-19; Nasopharynx; elektronické tranzistory; Biosensing Techniques; RNA virová; limita detekce; biosenzitivní techniky; Limit of Detection; design vybavení; Transistors, Electronic; Humans